Antipsychotic Use in Dementia: Is There a Problem and Are There Solutions?. (March 2017) - Kirkham, Julia; Sherman, Chelsea; Velkers, Clive; Maxwell, Colleen; Gill, Sudeep; Rochon, Paula; Seitz, Dallas
Antipsychotics are necessary for many older adults to treat major mental illnesses or reduce distressing psychiatric symptoms. Current controversy exists over the role of antipsychotics in the management of neuropsychiatric symptoms (NPS) in persons with dementia. Although some NPS may be appropriately and safely treated with antipsychotics, a fine balance must be achieved between the benefits of these medications, which are often modest, and adverse events, which may have significant consequences. Approximately one-third of all persons with dementia are currently prescribed antipsychotic medications, and there is significant variation in the use of antipsychotics across care settings and providers. Reducing the inappropriate or unnecessary use of antipsychotics among persons with dementia has been the focus of increasing attention owing to better awareness of the potential problems associated with these medications. Several approaches can be used to curb the use of antipsychotics among persons with dementia, including policy or regulatory changes, public reporting, and educational outreach. Recently, there has been encouraging evidence of a downward trend in the use of antipsychotics in many long-term care settings, although prescribing rates are still higher than what is likely optimal. Although reducing the inappropriate use of antipsychotics is a complex task, psychiatrists can play an important role via the provision of clinical care and research evidence, contributing to improved care of persons with dementia in Canada and elsewhere.